Fieldwork without the field: Navigating qualitative research in pandemic times - Gailloux, Chantal; Furness, Walter W.; Myles, Colleen C.; Wiley, Delorean S.; Collins, Kourtney (Frontiers in Sustainable Food Systems, 2022)
More than ever before, the COVID-19 pandemic has required qualitative researchers to develop open-ended, flexible, and creative approaches to continuing their work. This reality includes the adoption of open-ended research goals, a willingness to continually adapt to unpredictable and changing (viral) circumstances, and a commitment to opening toward and adhering to participants' preferences. This ethos is entrenched in a web of moral responsibility and a future anteriorized ethics. We reflect on pandemic-era ethical and methodological considerations in light of Fortun's studies of toxic contamination, research conducted in conflict settings, and researcher experiences during the early stages of COVID-19. Drawing from our own experiences and bearing in mind our own entangled web(s) of moral responsibility, we explore the future anteriorized ethics and methodological landscape of the “new normal” pandemic (potentially endemic) era. We reflect on what data we are able to gather and what data we dare to gather in the context of COVID-19, ultimately asking how qualitative researchers can maintain a safe and ethical environment for conducting research. To this end, we emphasize a recognition of our obligations to our research partners and ourselves in order to reduce risk by turning doubts and concerns into opportunities during project development and fieldwork and transforming participants into collaborators in spaces of uncertainty. Through targeted reflections on our processes of adaptation in research, we examine how scholars can perform relatedness, knowledge, reasonableness, and care in the midst of a risky, compromised research context.